New Perspectives on Microsoft Office PowerPoint 2007 - Beverly B. Zimmerman (Cengage Learning, Inc, 2008)
Following the critical thinking, problem-solving approach of the New Perspectives Series students will gain a comprehensive understanding of Microsoft PowerPoint 2007, including the new features of the software. The case-based tutorials challenge students to apply what they are learning to real-life tasks, preparing them to easily transfer skills to new situations. With the New Perspectives Series approach, students understand why they're learning what they're learning, and are better situated to retain skills